2020
DOI: 10.3389/fmicb.2020.00550
|View full text |Cite
|
Sign up to set email alerts
|

Captivity Influences Gut Microbiota in Crocodile Lizards (Shinisaurus crocodilurus)

Abstract: Captivity is an important measure for conservation of an endangered species, and it is becoming a hot topic in conservation biology, which integrates gut microbiota and endangered species management in captivity. As an ancient reptile, the crocodile lizard (Shinisaurus crocodilurus) is facing extreme danger of extinction, resulting in great significance to species conservation in the reserve. Thus, it is critical to understand the differences in gut microbiota composition between captive and wild populations, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

10
54
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(64 citation statements)
references
References 70 publications
10
54
0
Order By: Relevance
“…Our data showed that in both species the most functionally distinct categories were focused on metabolism, genetic information processing and environmental information processing at the first function level, followed by gene functions associated with membrane transport, replication and repair, amino acid metabolism and carbohydrate metabolism at the second level, and transporters and ABC transporters at the third level. In reptiles, that the gene functions of the gut microbes are associated with metabolism has been reported for the timber rattlesnake Crotalus horridus ( Mclaughlin, Cochran & Dowd, 2015 ), the crocodile lizard Shinisaurus crocodilurus ( Tang et al, 2020 ), and the northern grass lizard Takydromus septentrionalis ( Zhou et al, 2020 ). Similar results have also been reported for birds ( Wang et al, 2018 ) and mammals ( Zhao et al, 2018 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our data showed that in both species the most functionally distinct categories were focused on metabolism, genetic information processing and environmental information processing at the first function level, followed by gene functions associated with membrane transport, replication and repair, amino acid metabolism and carbohydrate metabolism at the second level, and transporters and ABC transporters at the third level. In reptiles, that the gene functions of the gut microbes are associated with metabolism has been reported for the timber rattlesnake Crotalus horridus ( Mclaughlin, Cochran & Dowd, 2015 ), the crocodile lizard Shinisaurus crocodilurus ( Tang et al, 2020 ), and the northern grass lizard Takydromus septentrionalis ( Zhou et al, 2020 ). Similar results have also been reported for birds ( Wang et al, 2018 ) and mammals ( Zhao et al, 2018 ).…”
Section: Discussionmentioning
confidence: 99%
“…For example, early growth, household location, and antibiotic experiences during pregnancy are correlated with the early gut microbial composition in humans ( Vatanen et al, 2019 ). Seasonal variation in diets may lead to changes in the gut microbiota ( Kartzinel et al, 2019 ), and exposure of host animals to artificial environments (e.g., animals in captivity) may lead to an increase in the abundance of human disease-related functional genes in the gut microbes ( Tang et al, 2020 ; Zhou et al, 2020 ). Taken together, the gut microbial community is affected by the host’s genetic background, diets and individual status and, in turn, affects the physiological, behavioral and even evolutionary processes of the host.…”
Section: Introductionmentioning
confidence: 99%
“…The lizrads’ gut microbial community compositions and structures were similar to those observed in mammals, and previous studies have documented general patterns. Further, gut bacterial diversity did not depend on the diversification of lizard hosts [ 33 ], but it varied along altitudes, diet and captive environment [ 2 , 14 , 34 , 35 , 36 , 37 , 38 ], and changed due to climate warming [ 32 ]. There was no significant difference in gut bacterial diversity between juveniles and adults [ 35 ], but males had significantly higher gut bacterial diversity and richness than do females [ 39 ], while non-gestation females had higher gut bacterial richness than do late-gravid females [ 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…The microbiome composition differs between the large intestine and small intestine in Agkistrodon piscivorus [ 42 ]. However, the differences in the relative abundance in Shinisaurus crocodilurus were reported, such as Bacteroidetes (32.1%) and Proteobacteria (47.9%) were the dominant phyla in the cloacal swab samples [ 38 ], whereas Firmicutes (61.2%) and Proteobacteria (35.8%) were the dominant phyla in fecal samples [ 35 ]. The majority of these studies have been conducted using fecal samples, cloaca swabs, or the intestinal contents collected from wild-caught or captive individuals.…”
Section: Introductionmentioning
confidence: 99%
“…A common objective of animal studies has been to explore the extent of bacterial community perturbations in the gut caused by anthropogenic intervention and investigate resulting ramifications on animal fitness and longevity [ 13 , 14 , 15 , 16 , 17 , 18 ]. Recent investigations have focused on comparing gut microbiota of captive animals and their wild counterparts in order to assess links to the captive lifestyle [ 14 , 19 , 20 , 21 ]. Roles of microbiota on host survival upon release have also been examined.…”
Section: Introductionmentioning
confidence: 99%